Is Chinaʼs Capital Liberalisation Policy Effective? - Lirong Wang; Jinnan Zhou; C. James Hueng (Asia & the Pacific Policy Studies, 2025)
ABSTRACT Chinaʼs comprehensive administrative system for capital controls and ongoing capital liberalisation are unique features compared with other emerging economies. These allow us to investigate the effects of Chinaʼs capital controls and subsequent liberalisation policies, along with various global‐push and domestic‐pull factors, on its gross capital flows in a time series analysis. We collect various sources of information on Chinaʼs capital control policies from 2005 to 2022 and construct quarterly time series of Chinaʼs capital control indices for different types of gross flows. Using the bounds tests of cointegration and a conditional error‐correction model, we show that Chinaʼs capital account liberalisation successfully encourages foreignersʼ investments aiming at production to maintain a long‐term relationship with China, as well as their short‐term financial investments to China. On the other hand, Chinese residents increase their long‐term investments overseas during the liberalisation process. However, their portfolio investments abroad are not responsive to the relaxation of capital controls.